1998
DOI: 10.1086/301907
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That a Locus for Familial High Myopia Maps to Chromosome 18p

Abstract: Myopia, or nearsightedness, is the most common human eye disorder. A genomewide screen was conducted to map the gene(s) associated with high, early-onset, autosomal dominant myopia. Eight families that each included two or more individuals with >=-6.00 diopters (D) myopia, in two or more successive generations, were identified. Myopic individuals had no clinical evidence of connective-tissue abnormalities, and the average age at diagnosis of myopia was 6.8 years. The average spherical component refractive erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
119
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 39 publications
3
119
0
2
Order By: Relevance
“…The increased eye diameter observed in Lama1 ⌬ homozygotes also suggests a possible link to myopia, which is associated with increased eye size (53). Interestingly, a locus for high grade myopia-2 maps to a region on human chromosome 18 that contains LAMA1 (54,55). Finally, mutations in LAMB2 have recently been shown to cause Pierson disease, in which patients experience microcoria (narrowing of the pupils) as well as kidney and central nervous system abnormalities clinically characterized by microcoria (fixed narrowing of the pupils) (56).…”
Section: Discussionmentioning
confidence: 99%
“…The increased eye diameter observed in Lama1 ⌬ homozygotes also suggests a possible link to myopia, which is associated with increased eye size (53). Interestingly, a locus for high grade myopia-2 maps to a region on human chromosome 18 that contains LAMA1 (54,55). Finally, mutations in LAMB2 have recently been shown to cause Pierson disease, in which patients experience microcoria (narrowing of the pupils) as well as kidney and central nervous system abnormalities clinically characterized by microcoria (fixed narrowing of the pupils) (56).…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary [17][18][19][20][21][22] and environmental [23][24][25] factors have been postulated to be responsible for myopia and myopic progression. Our study found that the incidence of children who revealed myopic progression or stability, or even regression may be related to whether or not their parent(s) suffered from myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Porém, a dificuldade no diagnóstico diferencial com outras alterações genéticas como a síndrome de Marshall ou fenótipo Marshall/ Stickler (21) , síndrome de Wagner (20,23) , alta miopia familial (26) , subestima o número de pacientes com síndrome de Stickler.…”
Section: Discussionunclassified
“…Toda miopia em criança deve ser acompanhada com muito cuidado, sempre pesquisando alterações sistêmicas, já que muitas são as síndromes genéticas que cursam com miopia congênita, dentre elas: síndrome de Down, síndrome de Marfan, homocistinúria, síndrome de Ehlers-Danlos, síndrome de Stickler, síndrome de Pierre-Robin, síndrome de Prader-Willi, síndrome de Noonan entre outras (26,28) . A miopia presente na SS tipo II é descrita normalmente como não progressiva.…”
Section: Discussionunclassified